Kemiskinan Global Dalam Prespektif 'Development as Freedom' Amartya Sen Kasus: Indonesia - P.Y. Nur Indro (Parahyangan Center for International Studies, 2013)
On poverty reduction is the ultimate goal of human development globally. Amartya Sen offers a perspective known as Development as Freedom, which prioritizes freedom as a goal and instrument development. Categories of development success, especially in humans as subjects who have an ever increasing freedom.Keywords : freedom, development, poverty, autonomy of human